2016
DOI: 10.1007/s10964-016-0456-8
|View full text |Cite
|
Sign up to set email alerts
|

The Enduring Significance of Skin Tone: Linking Skin Tone, Attitudes Toward Marriage and Cohabitation, and Sexual Behavior

Abstract: Past evidence has documented that attitudes toward marriage and cohabitation are related to sexual behavior in adolescence and young adulthood. This study extends prior research by longitudinally testing these associations across racial/ethnic groups and investigating whether culturally relevant variations within racial/ethnic minority groups, such as skin tone (i.e., lightness/darkness of skin color), are linked to attitudes toward marriage and cohabitation and sex. Drawing on family and public health literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Likewise, as the current study findings, it also showed that cultural norms and belief of finding a partner is linked with the color of the skin. Landor & Halpern (2016) also corroborate the present study results stating that skin color acts as a determiner of marriage, which eventually promotes the use of skin whitening products. Hamilton, Goldsmith, & Darity (2009) also endorse the idea and stated it as a promoter of the usage among individuals, particularly females.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, as the current study findings, it also showed that cultural norms and belief of finding a partner is linked with the color of the skin. Landor & Halpern (2016) also corroborate the present study results stating that skin color acts as a determiner of marriage, which eventually promotes the use of skin whitening products. Hamilton, Goldsmith, & Darity (2009) also endorse the idea and stated it as a promoter of the usage among individuals, particularly females.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, it is mundane, because this stress is so common, a part of the day-to-day experience of all Blacks that it is almost taken for granted; extreme, because it has a harsh impact on the psyche and world view of Blacks (e.g., self-perception, behavior, interactions); environmental, because it is environmentally induced and fostered; stress, because the ultimate impact on African Americans and their families is indeed stressful, detracting and energy-consuming. (Carroll, 1998, p. 271) Thus, MEES is an additional burden that African Americans and their families carry daily 1 Colorism is a form of discrimination based on an individual's skin tone (i.e., lightness or darkness of skin color) rather than race or ethnicity (Landor & Halpern, 2016). Colorism is a social implication of skin tone that results in the allocation of privileges and advantages based on one's skin tone.…”
Section: Stress Modelmentioning
confidence: 99%
“…Colorism is a form of discrimination based on an individual's skin tone (i.e., lightness or darkness of skin color) rather than race or ethnicity (Landor & Halpern, ). Colorism is a social implication of skin tone that results in the allocation of privileges and advantages based on one's skin tone.…”
mentioning
confidence: 99%
“…Research has shown that, among African Americans, individuals with lighter skin are often preferred over darker skinned counterparts as potential mates (Landor & Halpern, 2016). Thus, we control for observer-rated skin tone (Landor et al, 2013).…”
Section: Methodsmentioning
confidence: 99%